The humanization of birth as a tool in the fight against obstetric violence: A reflective theoretical study (Research, Society and Development, 2021)
The objective was to contribute to the expansion of knowledge of the general population, especially women and the academic community, about the humanization of childbirth and obstetric violence. Reflective theoretical study, descriptive with a qualitative approach, the following databases were used for its execution: SCIELO, BVS, which is integrated with other databases such as LILACS, PAHO, WHOLIS and PUBMED. A total of 33 articles were selected, 3 of which were international and 30 of national origin. Mostly cross-sectional and descriptive studies with a qualitative approach. As inclusion criteria, original articles in Portuguese and English were used, respecting the publication time limit between 2011 and 2021. The themes that guided the research were: obstetric violence; prenatal care: preparation for childbirth, education of the pregnant woman and insertion of the partner/father; humanization in the pregnancy-puerperal period; role of the nurse and awareness of the team for humanization; knowledge of women about their rights during pregnancy and puerperal period. The importance of sensitizing the team, carrying out more research on these themes by professionals and by academics was perceived, so that the knowledge of the entire population could be expanded.